(untitled) (MIST International Journal of Science and Technology, 2022)
Numerical study is presented in this work for turbulent cavitating flow pattern simulation on a hydrofoil, using state equation of cavitation model along with combined turbulence model for mixed fluid based on commercial software FLUENT 6.0. This solver is based on finite volume method. Cavitating study yield irregular behavior with the variation of cavitation values ( . This study is focused on pressure variation, vapor volume fraction, lift and drag forces on the foil section for various cavitation values at angle of attack. Cavitation initiation begins at the foremost surface and covers towards the end chord with reducing cavitation value. Moreover, the change of vapor region pattern is predicted towards the front of the foil. Finally, transitional flow range is observed for values 0.8 to 1.2 with large standard deviation. MIJST, Vol. 10, December 2022: 11-19 DOI: https://doi.org/10.47981/j.mijst.10(03)2022.351(11-19)